A pneumatological approach to transformational development: Implication for the church - Kakwata, Frederick (Stellenbosch Theological Journal, 2018)
This article seeks to articulate a biblical pneumatological approach to transformational development. The aim is to explore and examine the work of the Holy Spirit in Grudem's perspective and how it relates to transformational development. It is argued that the work of the Holy Spirit and the integral human development it brought amongst the early Christian community can function as a paradigm for the contemporary church globally, and particularly in Africa engaging in developmental work as well as for subsequent generations of Christians dealing with issues of transformation development.
Free
Keywords: Holy Spirit; Pneumatology; church; development; transformation